2020
DOI: 10.5173/ceju.2020.0265.r1
|View full text |Cite
|
Sign up to set email alerts
|

Obesity leads to a higher rate of positive surgical margins in the context of robot-assisted radical prostatectomy. Results of a prospective multicenter study

Abstract: Introduction Current results concerning the effect of body mass index (BMI) on positive surgical margins (PSMs) after robot-assisted radical prostatectomy (RARP) in patients with localized prostate cancer are inconsistent. Therefore, the aim of this study was to further analyse the association between BMI and PSMs after RARP. Material and methods Between March 2017 and December 2017 a multicentre, prospective, randomised, single-blind series with a blinded outcome asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Student et al and Sforza et al confirmed this finding with their multivariate analyses, demonstrating an OR of 1.1 and 1.7, respectively [20,26]. Intraoperative challenging conditions and chronic inflammation in the adipose tissue could provide reasons for the higher risk of postoperative LC and sLC [25][26][27][28]. BMI was also found to be an independent predictor of Clavien 3 complications in patients undergoing RARP with extended PLND [29].…”
Section: Discussionmentioning
confidence: 86%
“…Student et al and Sforza et al confirmed this finding with their multivariate analyses, demonstrating an OR of 1.1 and 1.7, respectively [20,26]. Intraoperative challenging conditions and chronic inflammation in the adipose tissue could provide reasons for the higher risk of postoperative LC and sLC [25][26][27][28]. BMI was also found to be an independent predictor of Clavien 3 complications in patients undergoing RARP with extended PLND [29].…”
Section: Discussionmentioning
confidence: 86%
“…Furthermore, the median BMI of NHT cases was significantly higher than that of standard NNHT cases (30 vs. 28, respectively) (p = 0.045). However, obesity in patients undergoing RARP is associated with more difficult intraoperative courses, elevated rates of case abortion, unfavorable postoperative outcomes, increased operating time, reduced nerve-sparing technique, and higher rates of positive surgical margins [20][21][22][23]. Within our cohort, the operating time and catheter days were longer in NHT patients, which may also be influenced by higher BMIs and not merely the high-risk tumor characteristics or the use of neoadjuvant hormonal therapy.…”
Section: Discussionmentioning
confidence: 73%